Exploring the Link between Attachment Styles, Empathy Development, and Moral Decision-Making in Adolescents: A Comparative Study of Rural and Urban Areas of Punjab - Khan, Dr. Aqeel Ahmad; Altaf, Rabeeya; Khan, Gull Naz; Jamil, Bisma; Fatima, Umbreen; Khalil, Aroosa; Ikram, Ahmed (South Eastern European Journal of Public Health, 2025)
This study explores the relationship between attachment styles, empathy development, and moral decision-making among adolescents, with a comparative focus on rural and urban areas of Punjab. Using a cross-sectional design, data were collected from 400 adolescents (200 rural, 200 urban) aged 13–18 years. Standardized instruments, including the Attachment Style Questionnaire (ASQ), Interpersonal Reactivity Index (IRI), and a series of hypothetical moral dilemmas based on Kohlberg’s framework, were used to measure the key variables. Results indicated that secure attachment positively correlated with both empathy (r = 0.62, p < 0.01) and advanced moral reasoning, while anxious and avoidant attachment styles showed negative associations. Empathy emerged as a significant predictor of moral decision-making (β = 0.38, p < 0.01), with rural adolescents exhibiting higher empathy levels compared to their urban counterparts (t = 4.23, p < 0.01). Although urban adolescents demonstrated a slight tendency toward post-conventional moral reasoning, overall moral decision-making scores were comparable across groups. The combined impact of attachment styles and empathy was significant, highlighting their interdependence in shaping adolescents’ ethical judgments. These findings underscore the importance of fostering secure attachment and empathy to promote moral development and provide practical implications for education and policy tailored to diverse socio-cultural contexts.